Public theology in cultural engagement - Holmes, Stephen R. (Milton Keynes, UK ; Colorado Springs, CO : Paternoster, 2008)
"Public Theology offers foundational and programmatic chapters exploring helpful ways to theologise about culture with missional intent. The book opens with three chapters taking steps towards developing a general theology of culture. Part Two explores the contribution of key biblical themes - creation, law, election, Christology, and redemption - to a theology of culture. The final section considers past and present theological proposals for engagement with culture, alongside contemporary reflections on nationalism and on drug culture."--BOOK JACKET.
Papers collected from two conferences held in 2002 and 2003 as a result of a "partnership project between the Research Institute in Systematic Theology at King's College London and the British and Foreign Bible Society"--Intro. p. [ix].
Includes bibliographical references.
Keywords: Christianity and culture; Church and social problems